2018
DOI: 10.1111/ijfs.13961
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in flavonol glycosides during production of green, yellow, white, oolong and black teas from Camellia sinensis L. (cv. Fudingdabaicha)

Abstract: Summary Flavonol glycosides with low thresholds are important flavour substances in tea leaves. This study monitored the dynamic changes in flavonol glycosides during the production of different teas. The fresh leaves of cv. Fudingdabaicha with 15.77 mg g−1 of total flavonol glycosides (TFG) were respectively processed into green, yellow, white, oolong and black teas. A reduction of TFG was observed for different teas, amongst which black tea contained the lowest level of TFG (9.83 mg g−1), followed by oolong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 29 publications
3
46
0
Order By: Relevance
“…Likewise, SNV method used for the mathematical transformation of the log (1/R) spectra used for scattering effects correction and to remove slope variation. SNV preprocessed NIR spectroscopy data were fed into chemometrics algorithm for searching relevant variables and subsequent model building which can be seen in Figure 2 (Chen, Zhao, & Lin, 2009;Fang et al, 2019;Li, Chen, Zhao, & Wu, 2015).…”
Section: Acquisition and Preprocessing Of Nir Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, SNV method used for the mathematical transformation of the log (1/R) spectra used for scattering effects correction and to remove slope variation. SNV preprocessed NIR spectroscopy data were fed into chemometrics algorithm for searching relevant variables and subsequent model building which can be seen in Figure 2 (Chen, Zhao, & Lin, 2009;Fang et al, 2019;Li, Chen, Zhao, & Wu, 2015).…”
Section: Acquisition and Preprocessing Of Nir Datamentioning
confidence: 99%
“…Many studies has been reported previously with the advantages of tea such as a study on polysaccharides protective effect against hyperlipidemia (Chen, Sun, Dong, Shen, & Xu, ), inhibitory activity of tea polysaccharides (Li, Wang, Yuan, Pan, & Chen, ), anti‐hyperglycaemic effects (Lin et al, ) and role against hyperlipidemia (Mao et al, ), also effects the blood glucose level and glucose tolerance which performed on mice (Chen et al, ). The identified and unidentified metabolic changes in fermented black tea is indicative of the changes in the antioxidant properties (Dong et al, ; Kim et al, ) also the change in flavonols glycosides which considered important flavor substances during the various teas production was study by (Fang, Song, Xu, & Ye, ). The phenolic compounds and their metabolites present in tea significantly affect the sympathetic nervous system, postprandial insulin, and angiotensin I‐converting enzyme (Monteiro & Peluso, ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, leaves and flowers of tea plants ( Camellia sinensis L.) have received more attention as a natural material for production of health‐enhancing foods and beverages due to their several health benefits such as antioxidant, antitumor, antimicrobial, hypoglycemic, and immunomodulatory activities and also anti‐agent in cardiovascular disease (Fang, Song, Xu, & Ye, ; Pinto, ; Zhu, Huang, & Tu, ). Both tea flowers and tea leaves contain important phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Both tea flowers and tea leaves contain important phenolic compounds. For instance, Fang et al () reported that tea leaves of Camellia sinensis L. (cv. Fudingdabaicha) had 15.77 mg/g of total flavonol glycosides as important flavor substances.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, studies have been taken up on the changes in flavanol glycosides due to oxidation, other polymeric polyphenolic compounds like theabrownins. (Faang, Song, Xu, & Ye, ; Wang, Sarkanj, & Jurasovic, ). Duration, temperature, and relative humidity of air and oxygen availability in the air during fermentation are crucial factors responsible for formation of high levels of desired products (Obanda, Owuor, & Mangoka, ; Tang et al, ) and their effect on the formation and depletion of the oxidized compounds and their correlation with sensory quality has been the subject of many studies (Asil, Rabiei, & Ansari, ; Muthumani and Senthil Kumar, ; Obanda et al, ; Owuor, Obanda, Nyirenda, & Mandala, ; Tang et al, ).…”
Section: Introductionmentioning
confidence: 99%